Consumer perceptions and criteria for purchase of electric vehicles in South Africa - Molomo, Mangaliso (My University, 2018)
ABSTRACT The objective of this research was to explore the perceptions and purchase criteria of Electric Vehicles among consumers in South Africa. As the world transitions from the use of fossil fuel in motor vehicles to renewable sources of energy the contribution that this study aims to make is towards the understanding of the psyche of consumers in South Africa. The study concludes that although negative perceptions towards EVs exist related to convenience, driving range, social image impact and cost, perceived cost savings associated with fuel and maintenance are major motivating factors for consumers in South Africa. The findings of this study have implications on motor vehicle manufacturers and distributers in South Africa who will have to change the negative perceptions that consumers have towards EVs, as well as policy makers who would have to ensure that a conducive policy and legislative landscape exists to encourage the adoption of EVs in South Africa. The methodology used for this research is Qualitative. 12 semi-structured interviews were conducted with consumers and the interviews were transcribed to text for analysis. The interview transcripts were analysed which resulted in the emergence of 6 broad themes. First, respondents were concerned about whether the driving range of an Electric Vehicle would be sufficient to meet their long-distance needs; Second, respondents expressed concern about the reliability of South Africa’s power supply; Third, respondents said an Electric Vehicle would be the ideal urban vehicle; Fourth, respondents were saw Electric Vehicles as being good for the environment; Fifth, respondents expressed concern about whether an Electric Vehicle would be good for their social image; And finally, respondents were concerned about the cost of Electric Vehicles but they believe that Electric Vehicles offer the benefit of long-term savings in vehicle operating and maintenance costs. The findings revealed that South African consumers are apprehensive about the usefulness of Electric Vehicles as a primary household vehicle given their frequent need to drive long distances and the unavailability of battery charging infrastructure. However, as a secondary vehicle in the home an Electric Vehicle perceived as a viable option for shorter urban commutes. iii Most respondents acknowledged the importance of the role that the electrification of mobility will play in reducing the harmful impact of motor vehicle exhaust emissions in South Africa. However, the level of concern that South African consumers have for the environment has not developed to the extent that it influences their vehicle purchase decision. The findings also reveal that South African consumers are motivated to a large extent by the brand of the car that they buy over the function or utility that the vehicle offers. Respondents expressed significant concern about the impact of driving an Electric Vehicle on their social image. Finally, the findings reveal that South African consumers perceive Electric Vehicles to be more expensive to buy but cheaper to operate and maintain than conventional petrol or diesel cars.
MBA
Keywords: Consumers -- South Africa. Consumers' preferences -- South Africa.